2021
DOI: 10.3390/nu13113693
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lingonberry (Vaccinium vitis-idaea L.) Supplementation on Hepatic Gene Expression in High-Fat Diet Fed Mice

Abstract: The prevalence of nonalcoholic fatty liver disease (NAFLD) is growing worldwide in association with Western-style diet and increasing obesity. Lingonberry (Vaccinium vitis-idaea L.) is rich in polyphenols and has been shown to attenuate adverse metabolic changes in obese liver. This paper investigated the effects of lingonberry supplementation on hepatic gene expression in high-fat diet induced obesity in a mouse model. C57BL/6N male mice were fed for six weeks with either a high-fat (HF) or low-fat (LF) diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 104 publications
1
4
0
Order By: Relevance
“…Our findings are in line with those of Kowalska et al, who reported that lingonberry extract downregulates the gene expression of DGAT1 and other genes in the mouse adipocytes [25]. Additionally, Ryyti et al observed that supplementation of HFD with dry Finnish lingonberry powder significantly reduced hepatic mRNA expression of monoacylglycerol O-acyltransferase 1 (MGAT1), the enzyme that synthesizes diacylglycerols from monoacylglycerol [50].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in line with those of Kowalska et al, who reported that lingonberry extract downregulates the gene expression of DGAT1 and other genes in the mouse adipocytes [25]. Additionally, Ryyti et al observed that supplementation of HFD with dry Finnish lingonberry powder significantly reduced hepatic mRNA expression of monoacylglycerol O-acyltransferase 1 (MGAT1), the enzyme that synthesizes diacylglycerols from monoacylglycerol [50].…”
Section: Discussionsupporting
confidence: 92%
“…Pparγ also plays an important role in regulating lipid metabolism, especially in lipid production gene expression and liver lipid synthesis induced by HFD ( Liu et al, 2019 ). Pparγ can improve insulin sensitivity, inhibit lipolysis of adipose tissue, reduce the release of free fatty acids from central adipose tissue, and prevent ectopic fat deposition in the liver and pancreas ( Ryyti et al, 2021 ). Excess energy induces abnormal Pparγ activation in liver and then promotes the occurrence of hepatic fat deposition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have demonstrated TUBBs have a capacity of regulating lipid metabolism. In mice fed a high-fat diet, the expression of TUBB2A and TUBB6 were significantly increased [ 26 ]. In humans, TUBB was reported to increase the risk of dyslipidemia and predict hypertension [ 27 ].…”
Section: Discussionmentioning
confidence: 99%